Top–down assessment of the Asian carbon budget since the mid 1990s - R. L. Thompson (Nature Portfolio, 2016)
Land biosphere uptake of carbon is important in mitigating the anthropogenic increase in atmospheric CO2and its climate forcing. Here, the authors show that land biosphere uptake of carbon in Asia has increased substantially since the mid 1990s, likely owing to reforestation and regional climate change.